2013
DOI: 10.1186/1741-7015-11-115
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on evolutionary medicine: the relevance of microevolution for human health and disease

Abstract: Evolutionary medicine (EM) is a growing field focusing on the evolutionary basis of human diseases and their changes through time. To date, the majority of EM studies have used pure theories of hominin macroevolution to explain the present-day state of human health. Here, we propose a different approach by addressing more empirical and health-oriented research concerning past, current and future microevolutionary changes of human structure, functions and pathologies. Studying generation-to-generation changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 54 publications
3
36
0
Order By: Relevance
“…If the young individuals in the Stone Age had inhaled biomass smoke from fires and developed COPD in their early life, genetic predispositions to COPD would have been under strong negative selection pressure (fig. 2) [27]. Exertional dyspnea would have caused a decrease in physical activity, reducing the ability to survive circumstances, such as hunting and wars, thereby reducing the chances of reproduction.…”
Section: Evolutionary Constraints On Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the young individuals in the Stone Age had inhaled biomass smoke from fires and developed COPD in their early life, genetic predispositions to COPD would have been under strong negative selection pressure (fig. 2) [27]. Exertional dyspnea would have caused a decrease in physical activity, reducing the ability to survive circumstances, such as hunting and wars, thereby reducing the chances of reproduction.…”
Section: Evolutionary Constraints On Selectionmentioning
confidence: 99%
“…d x = A fraction of dying people of age x; S x = reproductive value of a person of age x (for example, S65 = 0, while S15 = 1). This figure illustrates that in the Stone Age there was a very significant opportunity for the process of natural selection because of high levels of differential mortality that allowed less than half of the individuals born to pass on their genes to the next generation, eliminating the other half [27]. …”
Section: Evolutionary Constraints On Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, yet from a translational research perspective, Crispel et al describe in a rat model how the age at weaning from lactation regulates life history, growth, body composition and maturational tempo [19]. Rühli and Henneberg highlight the fact that humans continue to evolve and that microevolutionary changes can be observed over a few generations, including changes that are brought about by improved medical care [20]. …”
Section: Editorialmentioning
confidence: 99%
“…The value of its discoveries for clinical medicine and medical research has been increasingly recognized (Alcock, 2012;Rühli and Henneberg, 2013). The field has revealed that humans are continuing to evolve in response to their environments and to shifts in the burden of disease over time.…”
mentioning
confidence: 99%